L'histoire du logement ouvrier à Hochelaga-Maisonneuve - Atelier d'histoire Hochelaga-Maisonneuve (L'Atelier, 1980)
Keywords: Hochelaga (quartier); Logement; Maisonneuve

Edmond Fournier, charpentier-menuisier à Montréal (1876-1946): la petite histoire d'une famille ouvrière sur des cartes postales - Fournier, Louis (Histoire Québec, 2017)
Number: 3
Keywords: Charpentiers; Famille; Menuisiers; Travail

Le marché Sainte-Anne au quotidien. Plus insalubre qu'il n'y paraît! - Roy, Christian (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Les maisons ouvrières de la rue Saint-Germain - Atelier d'histoire Mercier-Hochelaga-Maisonneuve (D'une track à l'autre, 2017)
issued: 2017-24-00
Keywords: Hochelaga (quartier); Logement; Quartiers

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

Une forme d'entraide populaire: histoire des sociétés québécoises de secours mutuels au 19e siècle - Petitclerc, Martin (Université du Québec à Montréal, 2004)
Keywords: Assurance; Banques; Pauvreté; Union Saint-Joseph

De l'exil à la communauté : une histoire de l'immigration haïtienne à Montréal 1960-1990 - Saint Victor, Alain (Université du Québec à Montréal, 2018)
Keywords: Haïtiens; Travail

De vieilles filles à célibataires : une enquête d’histoire orale au Québec, 1940 à 1970 - McNeil, Françoise (Université de Sherbrooke, 2020)
Keywords: Femmes; Mariage

Le genre d’une migration post-coloniale: de Meknès (Maroc) à Montréal (Québec) - Cohen, Yolande (Genre et Histoire, 2010)
Number: 6
Keywords: Femmes; Féminisme; Historiens; Juifs; Marocains

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 2
Keywords: Famille; Logement; Quartiers; Rosemont

Everyday Life at St Anne's Market. Very, Very Unsanitary! - Roy, Christian (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n38 Translators: _:n62447
Keywords: Archéologie; Marchés; Sainte-Anne (marché); Égouts

Le mouvement des squatters à Montréal, 1946-1947 - Choko, Marc H. (Cahiers d'histoire, 1982)
issued: 1982-21-00
Keywords: Logement

Histoires de plex à Montréal: cohabitation et solidarité intergénérationnelle - Gagnon, Guillaume (Université de Montréal, 2013)
Keywords: Locataires; Logement

L'histoire en deux temps des HLM à Montréal - Lachapelle, Jacques (ARQ - Architecture Québec, 2009)
Keywords: Logement

Les Italo-Montréalais [sic] et leur histoire (suite et fin) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2019)
issued: 2019-23-00
Keywords: Guerre; Idéologies; Italiens

L'alcool comme objet de l'histoire culturelle. Représentations et pratiques - Fournier, Mélanie (Les journaux québécois d'une guerre à l'autre. Deux états de la vie culturelle québécoise au XXe siècle, 2018)
Keywords: Action catholique; Alcool; Canada (Le); Montreal Witness; Prohibition; Tempérance

Le Domaine. Une belle histoire qui se poursuit... Les jardins du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc, 2002)
Keywords: Domaine Saint-Sulpice; Jardins

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
issued: 2020-22-00
Keywords: Chemins de fer; Musique; Noirs; Travail

Conforme? Une histoire sociale du vêtement masculin chez les élites de Montréal, 1837-1918 - Villeneuve, Louis-Étienne (Université du Québec à Trois-Rivières, 2016)
Keywords: Bourgeoisie; Vêtements

Dans la rue. Une histoire du FRAPRU et des luttes pour le logement au Québec - Saillant, François (Écosociété, 2024)
Keywords: Groupes populaires; Logement

Tragédie à LaSalle: l'explosion du 1er mars 1965 - Gravel, Denis; Boucher, Isabelle (Éditions Histoire Québec, 2016)
Keywords: Arrondissements; Incendies; LaSalle; Logement

Peut-on guérir d'un passé asilaire?: survol de l'histoire socio-organisationnelle de l'Hôpital Rivière-des-Prairies - Wallot, Hubert (Publications MNH, 2005)
Keywords: Enfants; Hôpital Rivière-des-Prairies; Hôpitaux psychiatriques

Toutes les femmes sont d'abord ménagères : histoire d'un combat féministe pour la reconnaissance du travail ménager : Québec 1968-1985 - Robert, Camille (Éditions Somme toute, 2017)
Keywords: Femmes; Féminisme; Groupes populaires

Ainsi va la ville - Blais, Andrée (Montréal, une histoire à suivre, 1992)
Translators: _:n3353
Keywords: Enseignes; Expositions

Le récit de la classe moyenne: la publicité des quotidiens montréalais, 1920-1970 - Couvrette, Sébastien (Leméac Éditeur, 2014)
Keywords: Montreal Star; Presse (La); Publicité

Surviving as a Widow in 19th - Century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
Number: 3
Keywords: Famille; Femmes; Veuvage

To Love, Honour and Obey: Wife-Battering in Working-class Montreal, 1869-1879 - Harvey, Kathryn (Urban History Review / Revue d'histoire urbaine, 1990)
Number: 2
Keywords: Famille; Femmes

Crise du logement et action catholique à Montréal, 1940-1960 - Collin, Jean-Pierre (Revue d'histoire de l'Amérique française, 1987)
issued: 1987-23-00
Keywords: Coopérative d'habitation de Montréal; Ligue ouvrière catholique; Logement

Habitat ouvrier et révolution industrielle: le cas du village St-Augustin - Lauzon, Gilles (Regroupement des chercheurs et chercheures en histoire des travailleurs et travailleuses du Québec, 1989)
Keywords: Logement; Quartiers; Saint-Augustin; Saint-Henri

Les banlieues résidentielles planifiées dans la région de Montréal après la Seconde Guerre mondiale. Un modèle en redéfinition? - Poitras, Claire (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Brossard; Candiac; Lorraine

Le réseau de régulation sociale montréalais - Fecteau, Jean-Marie; Harvey, Janice (Histoire de Montréal et de sa région, 2012)
Keywords: Communautés religieuses; Femmes; Hôpitaux; Pauvreté

Pauvreté et richesse dans la région montréalaise depuis l'après-guerre. Un paysage en mouvement - Séguin, Anne-Marie; Negron-Poblette, Paula; Apparicio, Philippe (Histoire de Montréal et de sa région, 2012)
Keywords: Gentrification; Pauvreté; Quartiers

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

Population, identités sociales et vie quotidienne - Gauvreau, Danielle (Histoire de Montréal et de sa région, 2012)
Keywords: Famille; Femmes; Irlandais; Mortalité; Travail; Veuvage

Les années dures de la crise - Taschereau, Sylvie (Histoire de Montréal et de sa région, 2012)
Keywords: Chômage; Communistes; Crise; Libéralisme; Pauvreté; Socialistes; Travail

Le travail et la classe ouvrière montréalaise au XIXe siècle - Petitclerc, Martin (Histoire de Montréal et de sa région, 2012)
Keywords: Chevaliers du Travail; Conseil des métiers et du travail de Montréal; Grande Association; Grèves; Pauvreté; Syndicats internationaux; Travail

Bâtir ensemble: historique du mouvement coopératif en habitation dans Hochelaga-Maisonneuve - Labrecque, Francine (Atelier d'histoire Hochelaga-Maisonneuve, 1986)
Keywords: Hochelaga (quartier); Logement; Maisonneuve; Quartiers

Lueur urbaine : réverbères, émotions et vie nocturne, années 1880 à 1910 - Kenny, Nicolas (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Rues; Électricité

Les coûts de la vie : genre, citoyenneté et politique des prix à Montréal dans les années 1940 - Fahrni, Magda (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Alimentation; Femmes; Prix; Épicerie

"La lutte contre l'accident". Risque et accidents dans un contexte de modernité industrielle - Fahrni, Magda (Pour une histoire du risque: Québec, France, Belgique, 2012)

Habiter un nouveau quartier ouvrier de la banlieue de Montréal; village Saint-Augustin (Municipalité de Saint-Henri) 1855-1881 - Lauzon, Gilles (Université du Québec à Montréal, 1986)
Keywords: Logement; Quartiers; Saint-Augustin; Saint-Henri

To Love, Honour and Obey, Wife-Battering in Working-Class Montreal, 1869-1879 - Harvey, Kathryn (Université de Montréal, 1991)
Keywords: Famille; Femmes

The Working-Class Family Economy: Montreal, 1861-1881 - Bradbury, Bettina (Université Concordia, 1984)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Travail domestique et crise économique. Les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Université de Montréal, 1990)
Keywords: Crise; Famille; Femmes

La promotion de l’hygiène privée: les autorités sanitaires de la province de Québec et la propagande hygiéniste en territoire québécois (1908-1946) - Angers, Daniel (Université de Sherbrooke, 1998)
Keywords: Mortalité; Publicité; Tuberculose

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Université d'Ottawa, 1991)
Keywords: Femmes; Prostitution

La condition ouvrière à Montréal à la fin du XIXième siècle, 1874-1896 - Bernier, Jacques (Université Laval, 1971)

Le problème de l'alcoolisme au Canada français: discours élitaires et mouvements sociaux - Glaude, Rolland (Université de Sherbrooke, 1995)
Keywords: Alcool; Médecine

Vivre dans un quartier ouvrier de Montréal vers 1930 - Lauzon, Gilles (Histoire Québec, 2017)
Number: 1
Keywords: Pointe-Saint-Charles; Quartiers

L’Escouade de la moralité juvénile de Montréal et la corruption des garçons dans les années 1940 - Myers, Tamara (Une histoire des sexualités au Québec au XXe siècle, 2012)
Keywords: Délinquance; Enfants

‘Tuer le taudis qui nous tuera’: l’importance du foyer familial pour la santé nationale, 1945-1960 - Bourbeau, Amélie (Cahiers d'histoire, 2004)
issued: 2004-24-00
Keywords: Logement; Pauvreté

L'entrée de la Pointe-aux-Trembles dans la modernité: le mouvement réformiste 1900-1930 - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2008)
Keywords: Pointe-aux-Trembles; Réformistes

Les politiques familiales au Québec. Une perspective historique - Baillargeon, Denyse (Lien social et Politiques, 1996)
issued: 1996-23-00
Keywords: Enfants; Famille; Femmes

Quelques fragments de modernité - Willis, John (Cap-aux-Diamants, 2014)
issued: 2014-21-00
Keywords: Bourgeoisie

Working [on Imperial] Families: Bettina Bradbury's Imperial Re(turn) - Henderson, Jarrett (Labour / Le travail, 2014)
Keywords: Famille; Historiens

Pigs, Cows, Boarders, and...: Brothels, Taverns, and the Household Economy in Nineteenth-Century Montreal - Poutanen, Mary Anne (Labour / Le travail, 2014)
Keywords: Famille; Femmes

"Don't I Long for Montreal": l'identité hybride d'une jeune migrante franco-américaine pendant la Première Guerre mondiale - Fahrni, Magda; Frenette, Yves (Histoire sociale / Social History, 2008)
Number: 81
Keywords: Américains; Femmes; Français

Le renforcement des normes sur la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children, 1882-1920 - Hébert, Fernand (Bulletin d'histoire politique, 1998)
issued: 1998-24-00
Keywords: Enfants; Famille; Femmes

Les couples aux marges du permis-défendu. Morale conjugale et compromis pastoral à Montréal dans les années 1960 - Gervais, Diane (Études d'histoire religieuse, 2004)
Number: 70
Keywords: Mariage

Feathering Her Nest in Nineteenth-Century Montreal - Olson, Sherry (Histoire sociale / Social History, 2000)
Number: 65
Keywords: Rues

Entre les rues Coloniale et Saint-Urbain. Les Juifs ashkénazes dans les années 1930 - Olazabal, J.-Ignace (Bulletin d'histoire politique, 2001)
issued: 2001-24-00
Keywords: Juifs

«The Anxious Waiting Ones at Home »: Deux familles canadiennes plongées dans le tourment de la Grande Guerre - Morin-Pelletier, Mélanie (Histoire sociale / Social History, 2014)
Number: 94
Keywords: Famille; Guerre

Folie, internement et érosion des solidarités familiales au Québec: une analyse quantitative - Cellard, André (Bulletin d'histoire politique, 2002)
issued: 2002-21-00/2002-22-00
Keywords: Famille; Hôpitaux; Hôpitaux psychiatriques

''Beaucoup trop Chicago'': la campagne de moralité publique montréalaise dans ses contextes internationaux - Lapointe, Mathieu (Bulletin d'histoire politique, 2015)
Number: 1
Keywords: Avocats; Criminalité; Réformistes

Vers un coopératisme social: la Ligue ouvrière catholique et la question du logement dans les années 1940 - Collin, Jean-Pierre (Histoire sociale / Social History, 1994)
Number: 53
Keywords: Ligue ouvrière catholique; Logement

Le "sou du pauvre": les municipalités, l'indigence et l'accès aux soins hospitaliers au début du XXe siècle à Montréal - Charest-Bourdon, Noémie; Petitclerc, Martin (Histoire sociale / Social History, 2018)
Number: 103
Keywords: Communautés religieuses; Hôpitaux; Pauvreté

Les " jeunes ", les " amazones ", les " célestes ": les figures de la panique morale sur les drogues à Montréal dans le journal La Patrie, entre 1921 et 1923 - Grenier, Amélie (Bulletin d'histoire politique, 2020)
issued: 2020-22-00
Keywords: Chinois; Criminalité; Femmes; Patrie (La); Réformistes

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Number: 112
Keywords: Famille; Logement; Mariage

Le Montréal juif – (2e partie) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2021)
issued: 2021-24-00
Keywords: Juifs

Montreal of Yesterday: A Snapshot of Jewish Life in Montreal During the Era of Mass Immigration - M. Baker, Zachary (An Everyday Miracle: Yiddish Culture in Montreal, 1990)
Keywords: Juifs; Medres; Israel Jonah

Lettres biologiques. Recherche sur la sexualité humaine. - Marie-Victorin, Frère (Boréal, 2018)
Keywords: Gauvreau; Marcelle; Marie-Victorin; Frère; Sexologie

Three Generations of Goode Family - Breslaw, Caroline (The Westmount Historian, 2021)
Number: 2
Keywords: Famille

Le Montréal juif – (4e partie et fin) - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Juifs

Re-Working Respectability: the Feminisation of Clerical Work and the Politics of Public Virtue in Early Twentieth-Century Montreal - Boyer, Kate (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Travail

Tangled Webs: Remarriage and Family Conflict in Nineteenth-Century Quebec - Gossage, Peter (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Famille; Mariage

Hôtels, tempérance et prohibition: l'alcool dans le quotidien des Pointeliers - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2010)
Keywords: Alcool; Hôtellerie; Pointe-aux-Trembles; Prohibition; Tempérance

La presse gaie au Québec: vecteur d'une communauté - Giguère, Nicholas (Relire les revues québécoises: histoire, formes et pratiques (XXe-XXIe siècle), 2021)
Keywords: Fugues (revue)

''Depuis que l'élément étranger s'est mêlé [...] à la première société française'': dynamiques de genre dans l'espace domestique élitaire canadien au XIXe siècle - Bachand, Marise (Une histoire de la politesse au Québec. Normes et déviances, XVIIe-XXe siècles, 2015)
Keywords: Bourgeoisie; Britanniques; Femmes; Marchand-Dandurand; Joséphine

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Leméac, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

The Goode House (The Westmount Historian, 2021)
Number: 2
Keywords: Conservation; Famille; Jardins; Patrimoine

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-23-00
Keywords: Logement

Little Burgundy: The Interwoven Histories of Race, Residence, and Work in Twentieth-Century Montreal - High, Steven (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-23-00
Keywords: Chemins de fer; Noirs; Petite-Bourgogne; Quartiers; Travail

De la démolition des taudis à la sauvegarde du patrimoine bâti (Montréal, 1954-1973) - Drouin, Martin (Urban History Review / Revue d'histoire urbaine, 2012)
issued: 2012-23-00
Keywords: Conservation; Patrimoine

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
issued: 1995-22-00
Keywords: Femmes; Mariage

Le déclin de la maison de fond de cour à Montréal, 1880–1920 - Carey, Luc (Urban History Review / Revue d'histoire urbaine, 2002)
issued: 2002-23-00
Keywords: Logement

La puissance paternelle et les cas de garde d’enfants au Québec, 1866-1928 - Fish, Cynthia S. (Revue d'histoire de l'Amérique française, 2004)
Number: 4
Keywords: Enfants; Famille

Cohabitation et déménagements en milieu ouvrier montréalais: Essai de réinterprétation à partir du cas du village Saint-Augustin (1871-1881) - Lauzon, Gilles (Revue d'histoire de l'Amérique française, 1992)
Number: 1
Keywords: Locataires; Logement; Quartiers; Saint-Augustin

Permeable Boundaries: Negotiation, Resistance, and Transgression of Street Space in Saint-Henri, Quebec, 1875-1905 - Lord, Kathleen (Urban History Review / Revue d'histoire urbaine, 2005)
issued: 2005-21-00
Keywords: Quartiers; Rues; Saint-Henri

"Pour se créer un avenir". Stratégies de couples montréalais au XIXe siècle - Olson, Sherry (Revue d'histoire de l'Amérique française, 1998)
Number: 3
Keywords: Famille

Avoir moins d’enfants au tournant du XX siècle: une réalité même au Québec - Gauvreau, Danielle; Gossage, Peter (Revue d'histoire de l'Amérique française, 2000)
Number: 1
Keywords: Famille; Fécondité

Industrial Efficiency, Social Order and Moral Purity: Housing Reform Thought in English Canada, 1900–1950 - Purdy, Sean (Urban History Review / Revue d'histoire urbaine, 1997)
Number: 2
Keywords: Logement; Réformistes

Elsie Reford, une bourgeoise montréalaise et métissienne. Un exemple de spatialisation des sphères privée et publique - Hébert, Karine (Revue d'histoire de l'Amérique française, 2009)
issued: 2009-23-00/2010-24-00
Keywords: Bourgeoisie

A Home away from Home: Defining, Regulating, and Challenging Femininity at the Julia Drummond Residence in Montreal, 1920–1971 - Kirkland, Elizabeth (Urban History Review / Revue d'histoire urbaine, 2006)
Number: 2
Keywords: Femmes; Logement

''Pour la personne la plus précieuse de votre vie''. Représentation des enfants dans la publicité et construction d'une norme sociale concernant la famille et l'enfance à Montréal (1944-1945) - Archambault, Jacinthe (Revue d'histoire de l'Amérique française, 2011)
issued: 2011-22-00
Keywords: Enfants; Famille; Presse (La); Publicité; Revue moderne (La)

Claims on Housing Space in Nineteenth-Century Montreal - Gilliland, Jason A.; Olson, Sherry (Urban History Review / Revue d'histoire urbaine, 1998)
Number: 2
Keywords: Famille; Logement; Mobilité résidentielle

Fréquenter les Gouttes de lait: l'expérience des mères montréalaises, 1910-1965 - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1996)
Number: 1
Keywords: Enfants; Femmes; Goutte de lait; Mortalité

Sur le chemin du paradis: les joies d’aimer, de croire et de s’accomplir de Marie-Louise Globensky (1849-1919) - Doucet, Sophie (Revue d'histoire de l'Amérique française, 2017)
Number: 3
Keywords: Bourgeoisie

"Le soleil de la prospérité actuelle ne luit pas pour tout le monde": les exclus de la société de consommation à Montréal, 1945-1975 - O’Neill, Stéphanie (Revue d’histoire de l’Amérique française, 2017)
Number: 4
Keywords: Pauvreté; Quartiers

Eau courante, toilettes à eau et dernières latrines à Montréal, 1856-1915 - Lauzon, Gilles (Revue d'histoire de l'Amérique française, 2020)
issued: 2020-21-00
Keywords: Aqueduc; Égouts

Enjeux politiques de la frontière entre salubrité et insalubrité dans l'habitation montréalaise des années 1930 - Racette, Jean-Christophe (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-22-00/2021-23-00
Keywords: Crise; Logement; Pauvreté

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-21-00
Keywords: Chemins de fer; Paysages

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

From Conversation to Contract: The Notary's Role in Nineteenth-Century Montreal - Olson, Sherry; Poutanen, Mary Anne (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Famille; Notaires

Vagabons [sic] et sans abris à Montréal: perception et prise en charge de l'errance, 1840-1925 - Aranguiz, Marcela (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 2000)
Keywords: Itinérance; Pauvreté

William Notman’s Portrait Photographs of the Wealthy English-speaking Girls of Montreal: Representations of Informal Female Education in Relation to John Ruskin’s “Of Queens’ Gardens” and Writings by and for Canadians from the 1850s to 1890s - Lerner, Loren Ruth (Revue d'histoire de l'éducation / Historical Studies in Education, 2009)
issued: 2009-23-00
Keywords: Bourgeoisie; Femmes

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
issued: 2020-24-00
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Le Plateau au temps de la guerre (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
issued: 2015-23-00
Keywords: Conscription; Femmes; Fusiliers Mont-Royal; Gares; Guerre; Houde; Camillien; Juifs; Maires; Plateau Mont-Royal; Quartiers; Roman; Tramways; Transport en commun

Vies de ruelles (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2015)
issued: 2015-22-00
Keywords: Incendies; Plateau Mont-Royal; Quartiers

Les communautés culturelles du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-22-00
Keywords: Allemands; Députés; Godin; Gérald; Grecs; Irlandais; Itinérance; Johns; Emmett (Père Pops); Juifs; Plateau Mont-Royal; Portugais; Poésie; Quartiers; Roumains

Rooms of Their Own: The Nurses' Residences at Montreal's Royal Victoria Hospital - Adams, Annmarie (Material History Review / Revue d’histoire de la culture matérielle, 1994)
issued: 1994-23-00
Keywords: Hôpitaux; Infirmières; Logement; Maxwell; Edward; Maxwell; William S.; Royal Victoria Hospital

Le Centre de services communautaires du Monastère (CSCM) - Loubert, Huguette (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Groupes populaires

Luttes pour le droit au logement sur le Plateau - Vallée, Bernard (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Crise; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

Gouttes de lait et soif de pouvoir: les dessous de la lutte contre la mortalité infantile à Montréal, 1910-1953. - Baillargeon, Denyse (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 1998)
Number: 1
Keywords: Enfants; Goutte de lait; Mortalité

Une culture du voyage. Chronique d'une maisonnée d'Ahuntsic (1925-1945) - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 5
Keywords: Automobile; Famille

Chronique d'une maisonnée d'Ahuntsic. La formation d'une institution au cours des années 1920 - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 7
Keywords: Famille; Mariage

D’abord, prendre en mains son panier d’épicerie - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 8
Keywords: Alimentation; Chaurès-Louard; Berthe; La Familiale; Logement; Épicerie

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Le haut des côtes était la zone. Le nord-est d'Ahuntsic entre 1932 et 1944 - Campeau, André (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Ahuntsic; Logement; Pauvreté; Quartiers

Enfin chez soi! - Archambault-Malouin, Diane; Beauchamp, Maurice; St-Marseille, Michel (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 9
Keywords: Coopérative d'habitation de Montréal; La Familiale; Logement; Sault-au-Récollet

Le Comité d’Habitation de Montréal - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Keywords: Ahuntsic; Groupes populaires; Logement

"Demandez à quelqu’un qui sait": discours des publicitaires et des experts de la famille sur les enfants et la consommation à Montréal au lendemain de la Deuxième Guerre mondiale (1944-1954) - Archambault, Jacinthe (Université du Québec à Montréal, 2007)
Keywords: Enfants; Famille; Publicité

La robe montréalaise bourgeoise, 1870-1883: clichés, tendances et contextes de consommation - Vallières, Nicole (Université Laval, 1999)
Keywords: Bourgeoisie; Vêtements

Une place à soi? Aspects du célibat féminin laïc à Montréal à la fin du 19e siècle - Renaud, Catherine (Université de Montréal, 1994)
Keywords: Femmes

Un type de maison ouvrière: le déclin de la maison de fond de cour à Montréal, 1880-1920 - Carey, Luc (Université du Québec à Montréal, 1996)
Keywords: Logement

Pour une politique de restauration familiale: une analyse du discours de l'école sociale populaire dans le Québec de l'entre-deux-guerres - Quesney, Chantale (Université du Québec à Montréal, 1998)
Keywords: Famille; École Sociale Populaire

La mendicité au centre-ville de Montréal: étude du paradoxe du mendiant - Touchette, Daniel (Université du Québec à Montréal, 1996)
Keywords: Itinérance; Pauvreté

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

La contribution, le rôle et la place des femmes au Service de préparation au mariage de Montréal, 1944-1972 - Pelletier, Anne (Université de Montréal, 1997)
Keywords: Femmes; Mariage

Différenciation sociale et rituels du mariage: les Montréalais francophones, 1925-1940 - Girard, Denise (Université Laval, 1998)
Keywords: Francophones; Mariage

Les accidents impliquant des enfants et l'attitude envers l'enfance à Montréal (1900-1945) - Cournoyer, Catherine (Université de Montréal, 2000)
Keywords: Enfants

Le suicide dans le district judiciaire de Montréal (de 1815 à 1843 et de 1893 à 1903) - Bordeleau, François (Université du Québec à Montréal, 2001)
Keywords: Mortalité

"C'est d'abord aux mamans à surveiller les dépenses de la maison": La ligue ouvrière catholique et la consommation quotidienne au Québec, 1939-1954 - Brisebois, Marilyne (Université Laval, 2011)
Keywords: Famille; Femmes; Ligue ouvrière catholique; Prix

To Indulge their Carnal Appetites: Prostitution in Early Nineteenth-Century Montreal, 1810-1842 - Poutanen, Mary Anne (Université de Montréal, 1997)
Keywords: Police; Prostitution; Tribunaux

Laveuse automatique et gâteau Duncan Hines: les impacts de la technologie domestique et des aliments à cuisson rapide sur la ménagère et sa représentation dans la publicité québécoise, 1945-1965 - Landry, Tara (Université du Québec à Montréal, 2000)
Keywords: Alimentation

Fous, prodigues et ivrognes: internormativité et déviance à Montréal au 19e siècle - Nootens, Thierry (Université du Québec à Montréal, 2003)
Keywords: Alcool; Famille; Hôpitaux; Hôpitaux psychiatriques; Médecine

Manliness, Goodness, and God: Poverty, Gender, and Social Reform in English-Speaking Montreal, 1890-1929 - Perry, Ann Kirsten (Université Queen's, 1998)
Keywords: Anglophones; Pauvreté; Réformistes

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

L'entraide au quotidien: l'exemple de la paroisse Ste-Brigide, Montréal, 1930-1945 - Bonnier, Lucie (Université du Québec à Montréal, 1996)
Keywords: Sainte-Brigide (paroisse)

Mobilizing Canada: the National Resources Mobilization Act, the Department of National Defence, and Compulsory Military Service in Canada - Byers, Daniel Thomas (Université McGill, 2000)
Keywords: Conscription; Guerre

Les Settlement Houses montréalais et les anglo-protestants. Un écho de la fin du XIXe siècle. Une lumière sur le XXe siècle - Leclair, Micheline (Université du Québec à Montréal, 2000)
Keywords: Anglophones; Protestants

Images and Reality of Fatherhood: a Case Study of Montreal's Protestant Middle Class, 1870-1914 - Fish, Cynthia (Université McGill, 1992)
Keywords: Famille; Protestants

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

Femmes, cuisines et consommation de masse au Québec, 1945-1960 - Fradet, Louise (Université Laval, 1989)
Keywords: Alimentation; Femmes

Sur le front intérieur. Les ménagères québécoises de la seconde guerre mondiale: rationnement et récupération - St-Onge, Mélissa (Université de Montréal, 2007)
Keywords: Femmes; Guerre

"It's Funny the Things You Remember": Memories of Gendered Childhood in Montreal during the Great Depression - Rebelo, Nancy Moniz (Université Concordia, 2007)
Keywords: Crise; Enfants

Under Reconstruction: the Family and the Public in Postwar Montréal, 1944-1949 - Fahrni, Magda (Université York, 2001)
Keywords: Famille; Guerre

Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (Université McGill, 2000)
Keywords: Quartiers; Rues; Saint-Henri

Cultural Diversity in Mile End: Everyday Interactions between Hasidim and Non-Hasidim - Alton, Caitlin J. (Université Concordia, 2011)
Keywords: Juifs; Mile End; Quartiers

Faith, Family, Female Education and Friendship: Retelling Louise Amelia Monk's Adolescence in Bourgeois Montreal, 1867-1871 - Brettler Vandervort, Jessica L. (Université Concordia, 2003)
Keywords: Bourgeoisie; Femmes

Une ville bien arrosée: Montréal durant l'ère de la prohibition (1920-1933) - Hawrysh, Michael (Université de Montréal, 2014)
Keywords: Alcool; Prohibition

Conseiller les mères sur l'éducation de leurs enfants pendant l'entre-deux-guerres. Les chroniques d'Odette Oligny - Gratton, Valérie (Université de Montréal, 2015)
Keywords: Enfants; Femmes; Journalistes

A captivating ''Open City'': the production of Montreal as a ''wide-open-town'' and ''ville ouverte'' in the 1940s and '50s - Kuplowsky, Adam (Université McGill, 2014)
Keywords: Alcool; Criminalité; Délinquance; Prostitution

L’argent ne fait pas le bonheur : les discours sur la société de consommation et les modes de vie à Montréal, 1945-1975 - O'Neill, Stéphanie (Université de Montréal, 2016)
Keywords: Famille; Femmes; Pauvreté

Culture urbaine et homosexualité : pratiques et identités homosexuelles à Montréal, 1880-1929 - Dagenais, Dominic (Université du Québec à Montréal, 2017)
Keywords: Places publiques; Police; Quartiers; Saint-Antoine; Saint-Jacques; Sainte-Marie; École littéraire de Montréal

La Babylone des marins : Marins hauturiers à Montréal 1851-1896 - Bélisle-Desmeules, David (Université de Montréal, 2016)
Keywords: Alcool; Navigation; Port; Taverne Joe Beef

Battez-vous, ne vous laissez pas affamer! : la lutte des sans-emploi et le Parti communiste du Canada durant la Grande Dépression à Montréal (1930-1935) - Marsan, Benoit (Université de Sherbrooke, 2013)
Keywords: Communistes; Crise; Groupes populaires; Partis politiques

"Toutes les femmes sont d'abord ménagères" : discours et mobilisations des féministes québécoises autour du travail ménager (1968-1985) - Robert, Camille (Université du Québec à Montréal, 2017)
Keywords: Femmes; Féminisme; Groupes populaires

De cuisinière à gastronome ou comment les représentations du fait alimentaire ont évolué au sein de l'émission Femme d'aujourd'hui de 1965 à 1982 - Demay, Anna (Université du Québec à Montréal, 2018)
Keywords: Alimentation; Radio-Canada; Télévision

Permanence et renouvellement des familles ouvrières: le cas du Village-aux-Oies et de la rue Forfar, 1901-1921 - Giguère, Charles-Robert (Université du Québec à Montréal, 2018)
Keywords: Famille; Locataires; Logement; Mobilité résidentielle; Villages

«Toujours je sens mon âme se balancer entre les joies et les peines»: le paysage émotionnel de Marie-Louise Globensky (1849-1919) observé à travers ses écrits personnels - Doucet, Sophie (Université du Québec à Montréal, 2019)
Keywords: Bourgeoisie; Femmes

Qui va payer pour les malades indigents?: la "philanthropie d'État", du sou du pauvre à l'assistance publique au Québec (1905-1930) - Charest-Bourdon, Noémie (Université du Québec à Montréal, 2018)
Keywords: Communautés religieuses; Hôpitaux; Pauvreté

Contrôler le logement, contrôler la Ville: l’intervention en matière de salubrité des logements à Montréal, 1930-1939 - Racette, Jean-Christophe (Université de Montréal, 2017)
Keywords: Crise; Logement; Pauvreté

Inner city montréalais et banlieue parisienne, politiques et stratégies de lutte contre la pauvreté urbaine : la politique de la ville à Hochelaga-Maisonneuve (Canada) et Saint-Denis (France), années 1960-début des années 2000 - Bréville, Benoît (Université du Québec à Montréal et Université Paris Panthéon-Sorbonne, 2011)
Keywords: Hochelaga (quartier); Maisonneuve (quartier); Pauvreté; Quartiers

L'implication sociale et politique de Jacques Couture à Montréal de 1963 à 1976 - Croteau, Martin (Université du Québec à Montréal, 2008)
Keywords: Communautés religieuses; Groupes populaires; Jésuites; Pauvreté; Quartiers; Élections

Le discours sur la sexualité, l’alimentation et l’apparence corporelle des adolescentes québécoises durant la décennie 1980 : analyse du magazine Filles d’Aujourd’hui - Dumont-Lévesque, Catherine (Université de Sherbrooke, 2021)
Keywords: Enfants; Femmes

History, Memory, and Struggle in Saint-Henri, Montreal - Burrill, Fred (Université Concordia, 2021)
Keywords: Saint-Henri; Travail

Social Transformation in Notre Dame de Grâce over the Long Sixties - Kastner, Jeffrey (Université McGill, 2023)
Keywords: Centres d'acceuil

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Jobs, Homes, and the Right to Exist: Neighbourhood Activism in Deindustrializing Toronto and Montreal, 1963-1989 - Vickers, Simon (Université de Toronto, 2021)
Keywords: Quartiers; Travail

The Voice of the Child Cries Out Against You: The 1912 Montreal Child Welfare Exhibition in its North American and Transnational Contexts - Vanier, Marie-Hélène (Université Concordia, 2024)
Keywords: Enfants; Exposition; Mortalité

La vie de château - Dugas, Marcel (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Château Dufresne; Golden Square Mile; Logement; Mount Stephen Club

L'habitation type. Évolution de l'immeuble locatif pour les quartiers ouvriers: le cas de Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Logement; Quartiers; Verdun

Les Madelinots à Verdun - Carbonneau, Pauline (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2005)
issued: 2005-21-00
Keywords: Quartiers; Verdun

La prohibition - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2010)
Number: 2
Keywords: Alcool; Cabarets; Prohibition; Quartiers; Verdun

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

La Ligue ouvrière catholique et l'essor du mouvement coopératif d'habitation dans le Québec urbain, au tournant des années 1950 - Collin, Jean-Pierre (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1992)
issued: 1992-23-00
Keywords: Ligue ouvrière catholique; Logement

Maîtresses de maison dépareillées? L'apprentissage du travail domestique à Montréal au début du siècle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
issued: 1991-22-00
Keywords: Enfants; Famille; Femmes

La famille ouvrière juive à Montréal à la fin du XIXe siècle: le travail et le rôle économique de ses membres - Soucy, Isabelle (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2000)
issued: 2000-23-00
Keywords: Famille; Juifs

Le Parti communiste du Canada, les sans-emploi et la Grande Dépression à Montréal: résistance, répression et solidarité, 1930-1935 - Marsan, Benoît (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2012)
issued: 2012-23-00
Keywords: Communistes; Crise; Groupes populaires; Partis politiques

La représentation de la famille dans la peinture figurative nord-américaine durant la première moitié de la guerre froide (1945-1968) : les cas de Fairfield Porter, d'Alex Colville et de Jean Paul Lemieux - Scott, Christophe (Université du Québec à Montréal, 2021)
Keywords: Famille; Peinture

Negotiating Bella Figura: Inside the Childhood Homes of Six Second-Generation Italian-Canadian Women in Montreal - Massa, Lisa (Université Concordia, 2022)
Keywords: Enfants; Femmes; Italiens

Étude sur l'évolution d'enfants âgés de 6 à 12 ans et de leur famille suivis par les services externes des centres de réadaptation pour jeunes en difficulté d'adaptation des Centres jeunesse de Montréal - Touchette, Luc (Université de Sherbrooke, 1999)
Keywords: Enfants

La crise économique des années trente et la qualité de la vie chez les montréalais d'ascendance française - Tremblay, Marc-Adélard (La revue Desjardins, 1976)
Number: 5
Keywords: Crise

Deviant Anonymous: Single Mothers at the Hôpital de la Miséricorde in Montreal, 1929-39 - Lévesque, Andrée (CHA / SHC, Historical Papers / Communications historiques, 1984)
Keywords: Femmes; Hôpital de la Miséricorde; Hôpitaux

Working Class Housing in Montreal, 1940-1980 - Melamed, Andy (Montreal Geographical Essays, 1981)
Keywords: Logement

La crise économique des années trente et la qualité de vie chez les Montréalais d'ascendance française - Tremblay, Marc-Adélard (Travaux et communications, volume III : Progrès technique et qualité de vie, 1977)
Keywords: Crise

Ségrégation résidentielle des personnes âgées à Montréal, 1961-1981 - Grenier, J.-F. (Société canadienne d'hypothèques et de logement, 1984)
Keywords: Logement

Croissance de la population et besoins en logement dans la zone métropolitaine de Montréal - Ferland, Yvan (Conseil des oeuvres de Montréal, 1967)
Keywords: Logement

Entre l'usine et la cuisine (Maison du Fier-Monde, 1984)
Keywords: Femmes; Travail

Revendications et actions de la C.S.N. sur le logement, 1920-1982 - Choko, Marc H. (Confédération des syndicats nationaux, 1982)
Keywords: Confédération des syndicats nationaux; Logement

Gender at Work at Home: Family Decisions, the labour Market and Girl's Contributions to the Family Economy - Bradbury, Bettina (Canadian and Australian Labour History. Toward a Comparative Perspective, 1990)
Keywords: Enfants; Famille; Femmes; Travail

The Fragmented Family: Family Strategies in the Face of Death, Illness, and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Family Bonds and Gender Divisions: Readings in the Sociology of the Family, 1988)
Keywords: Famille; Orphelinats

Le besoin de logement à Montréal - Germain, Denis (L'Actualité économique, 1961)
issued: 1961-01/1961-03
Keywords: Logement

The Fragmented Family: Family Strategies in the Face of Death, Illness, and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Childhood and Family in Canadian History, 1982)
Keywords: Famille; Orphelinats

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Cities and Urbanization. Canadian Historical Perspectives, 1990)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2. After Confederation, 1986)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (The Social Development of Canada - Readings, 1983)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1991)
Keywords: Crise; Famille; Femmes

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (CHA / SHC, Historical Papers / Communications historiques, 1979)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

La condition des travailleurs, 1851-1896 - Bernier, Jacques (Les travailleurs québécois, 1851-1896, 1973)

Population nocturne et diurne à Montréal - Beauregard, Ludger (Revue de Géographie de Montréal, 1964)
Number: 2

The City Below the Hill - Ames, Herbert Brown (University of Toronto Press, 1972)
Keywords: Griffintown; Pointe-Saint-Charles; Saint-Antoine; Sainte-Anne

L'économie familiale et le travail dans une ville en voie d'industrialisation: Montréal dans les années 1870 - Bradbury, Bettina (Maîtresses de maison, maîtresses d'école, 1983)
Keywords: Famille; Travail

L'action sociale de Marie Gérin-Lajoie, 1910-1925 - Proulx, Marcienne (Université de Sherbrooke, 1975)
Keywords: Gérin-Lajoie; Marie; Institut du Bon-Conseil

Structure familiale et pouvoir conjugal dans des familles haïtiennes de Montréal - Lasry, Jean-Claude; Frédérik, Mario (Canadian Ethnic Studies / Études ethniques au Canada, 1986)
Number: 2
Keywords: Famille; Haïtiens

Poverty in Montreal - Puxley, Evelyn (Dawson College Press, 1971)
Keywords: Pauvreté

Crise économique et contrôle social, 1929-1937: le cas de Montréal - Lariviere, Claude (Éditions coopératives Albert Saint-Martin, 1977)
Keywords: Crise

Scènes de rues à Montréal au siècle passé - Massicotte, E.-Z. (Les Cahiers des Dix, 1942)
Keywords: Rues

L'habitation à Montréal - Cousineau, A. (Revue trimestrielle canadienne, 1920)
Number: 21
Keywords: Logement

Le développement des groupes populaires à Montréal, 1963-1973 - Mcgraw, Donald (Éditions coopératives Albert Saint-Martin, 1978)
Keywords: Groupes populaires

Neighbourhood Economy and the Urban Housing Problem: Landlords and Tenants in a Working Class Montreal Locality - Fleming, C. E. B.; Krohn, R. G. (The Western Canadian Journal of Anthropology, 1972)
Number: 2
Keywords: Locataires; Logement

Absorbing Junior: the Use of Patent Medicines as abortifacients in Nineteenth Century Montreal - Gossage, Peter (The Register, 1982)
Number: 1
Keywords: Avortement; Femmes; Médecine

L'habitation à Montréal - Deschamps, Jean (L'Actualité économique, 1947)
Number: 3
Keywords: Logement

Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le travail, 1984)
issued: 1984-23-00
Keywords: Famille; Femmes

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Fous, prodigues et ivrognes. Familles et déviances au XIXe siècle - Nootens, Thierry (McGill-Queen's University Press, 2007)
Keywords: Délinquance; Famille; Tribunaux

Grossières indécences: pratiques et identités homosexuelles à Montréal, 1880-1929 - Dagenais, Dominic (McGill-Queen's University Press, 2020)
Keywords: Clubs; Criminalité; Enfants; Police; Quartiers

Rapport sur la question du logement à Montréal; phase 1 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2007)
issued: 2007-22-00
Keywords: Locataires; Logement; Pauvreté

Rapport sur la question du logement à Montréal; phase 2 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2008)
issued: 2008-21-00
Keywords: Locataires; Logement; Pauvreté

Alimentation, commerce et patrimoine: documenter les acteurs du Vieux-Montréal victorien 1850-1880 - Burgess, Joanne (Laboratoire d'histoire et de patrimoine de Montréal, 2016)
Keywords: Alimentation; Commerce de détail; Magasins; Patrimoine; Quartiers; Vieux-Montréal